(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This research paper is entitled: (The Problem of Educational Research: Its Concept, Methods of Selection, Evaluation, and Steps to Clarify It), and the researchers used the descriptive analytical approach, as it is the most appropriate for the research topic based on collecting information, analyzing it, discussing it, and reaching results and recommendations to address the problems surrounding the topic. The paper was divided into five main requirements: the first requirement is the concept of the research problem, the second is about the methods of selecting the research problem, the third is the main foundations and criteria for evaluating the research problem, the fourth is the steps to clarify the problem in educational research, and the fifth includes the results, recommendations, and a list of sources and references. Among the results of this paper: the necessity of raising the level of awareness among researchers about the importance of understanding the research problem more deeply, by strengthening guidance programs for researchers, and organizing training courses and seminars that highlight the methods of selecting problems in educational research.